POPULASI BAKTERI PADA FESES NEONATUS: PENELITIAN PENDAHULUAN - Wikaningrum, Riyani; T Rochani, Jekti; Djannatun, Titiek; Widiyanti, Dian (Jurnal Kedokteran YARSI, 2008)
Recent published data have outlined a relationship between the composition of the intestinal microflora and allergic inflammation, autoimmunity, chronic bowel inflammation, psychiatric, cognitive and behavioral disturbances. Factors influencing intestinal microflora are environment, genetic predisposition, diet, age, diseases, drugs, stressor. This preliminary study is to establish local reference of microbial flora in neonates. This study included samples taken from 20 neonates, age 1 ? 7 days, from a private hospital in Jakarta. All samples were sent to microbiology laboratory without transport media and processed immediately. Bacteriological cultures for aerob and anaerob bacteria were performed according to the standard methods. Aerob and anaerob bacterial species were isolated from all samples, ranged 2 ? 5 species per sample. Enterobacteriaceae were found to be dominant isolates (25% - 75%); followed by Streptococcus anhaemolyticus (60%), Staphylococcus epidermidis (40%), Staphylococcus aureus (5%),Clostridium difficile (5%), Bacteroides fragilis (5%), Bifidobacterium sp. (10%), Lactobacillus sp. (5%) and yeast (5%). These data indicated that aerob and facultative anaerob bacteria were predominant in neonates. However Bifidobacterium, Lactobacillus and Clostridium difficile could be found. Further studies are needed to confirm this finding using larger number of samples and involving various age group.